Hypoglycemic and Hypolipidemic Effects of Cucumber, White Pumpkin and Ridge Gourd in Alloxan Induced Diabetic Rats - Sharmin, R.; Khan, M. R. I.; Akhtar, Most. A.; Alim, A.; Islam, M. A.; Anisuzzaman, A. S. M.; Ahmed, M. (Journal of Scientific Research, 2012)
Ethanolic extracts of some fruits of Cucurbitaceae family such as Cucumis sativus (cucumber), Lagenaria siceraria (white pumpkin), Luffa acutangula (ridge gourd), Benincasa hispida (ash gourd), Citrullus lanatus (sweet melon) and Cucarbita maxima (pumpkin) have been studied for their hypoglycemic effects on alloxan induced diabetic rats (AIDRs). Screening results suggested that among the tested fruits the hypoglycemic potency follows: cucumber > white pumpkin > ridge gourd. These three fruit-extracts were further investigated for their hypoglycemic, hypolipidemic and glycogenesis effects. Cucumber, white pumpkin and ridge gourd extracts reduced blood glucose level by 67, 65 and 51%, respectively at 12 hours after single intraperitoneal injection; while reduced the low density lipoprotein (LDL) level to 13, 28 and 86%, respectively in AIDRs. The maximum reduction 87% was observed by cucumber extract. Cucumber, white pumpkin and ridge gourd extracts reduced total cholesterol level to 29, 15 and 38%, respectively comparing with the diabetic control group. Here the maximum reduction of 85% was observed by white pumpkin extract. Cucumber, white pumpkin and ridge gourd also reduced triglyceride levels to 72, 68 and 80%, respectively. Maximum reduction of 32% was observed by white pumpkin. Significant improvement of glycogenesis was also observed by ridge gourd extracts in AIDRs. © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v5i1.10252 J. Sci. Res. 5 (1), 161-170 (2013)